SENSORY CHARACTERISTICS OF SHEREDDED SPICED FISH FORMULATIONS WITH DIFFERENT PROCESSING TREATMENTS - Sartika, Dewi; Akhyar, Gusri; Julita, Sela (AQUASAINS, 2024)
Tilapia (Oreochromis niloticus) is a type of fish cultivated by local people in Lake Ranau, West Lampung Regency, Lampung Province. Fish is easily damaged by chemical and microbiological processes, so proper handling and processing is needed to extend its shelf life. Shredded spiced fish is an innovative diversification of shredded fish product made from tilapia fish ori-ginating from Lake Ranau with added of multi-spices. Multi-spices are known to have high antioxidant content, so they can improve the quality and develop the taste of shredded spiced fish product.  The multi spices seasoning formulation and process stages greatly influence the characteristics of the shredded produced.  This research aims to study the formulation and processing treatment of the sensory characteristics of the best shredded spices fish. Determining the best formulation and processing treatment was determined using the sensory test method, namely a scoring test involving 30 panelists, then the data was processed using Microsoft Excel 2021. The result showed that the shredded spiced fish product with sample code 212 (without stir-frying) produced the best characteristics with a texture parameter value of 3.85; fragrance 4.05; colors 4.85; and tasted 4 with a total score of 16.75. Keywords: Multi spices, organoleptic, process stages, sheredded fish, tilapia.